The Kcnq1ot1 long non-coding RNA affects chromatin conformation and expression of Kcnq1, but does not regulate its imprinting in the developing heart. - Lisa Korostowski (PLoS Genetics, 2012)
Although many of the questions raised by the discovery of imprinting have been answered, we have not yet accounted for tissue- or stage-specific imprinting. The Kcnq1 imprinted domain exhibits complex tissue-specific expression patterns co-existing with a domain-wide cis-acting control element. Transcription of the paternally expressed antisense non-coding RNA Kcnq1ot1 silences some neighboring genes in the embryo, while others are unaffected. Kcnq1 is imprinted in early cardiac development but becomes biallelic after midgestation. To explore this phenomenon and the role of Kcnq1ot1, we used allele-specific assays and chromosome conformational studies in wild-type mice and mice with a premature termination mutation for Kcnq1ot1. We show that Kcnq1 imprinting in early heart is established and maintained independently of Kcnq1ot1 expression, thus excluding a role for Kcnq1ot1 in repressing Kcnq1, even while silencing other genes in the domain. The exact timing of the mono- to biallelic transition is strain-dependent, with the CAST/EiJ allele becoming activated earlier and acquiring higher levels than the C57BL/6J allele. Unexpectedly, Kcnq1ot1 itself also switches to biallelic expression specifically in the heart, suggesting that tissue-specific loss of imprinting may be common during embryogenesis. The maternal Kcnq1ot1 transcript is shorter than the paternal ncRNA, and its activation depends on an alternative transcriptional start site that bypasses the maternally methylated promoter. Production of Kcnq1ot1 on the maternal chromosome does not silence Cdkn1c. We find that in later developmental stages, however, Kcnq1ot1 has a role in modulating Kcnq1 levels, since its absence leads to overexpression of Kcnq1, an event accompanied by an aberrant three-dimensional structure of the chromatin. Thus, our studies reveal regulatory mechanisms within the Kcnq1 imprinted domain that operate exclusively in the heart on Kcnq1, a gene crucial for heart development and function. We also uncover a novel mechanism by which an antisense non-coding RNA affects transcription through regulating chromatin flexibility and access to enhancers.